Cushing’s Disease Presenting with Functional Neurological (Conversion) Disorder - Ashrafzadeh, Sahar; Mariano, Maria Theresa; Syed, Saba (Case Reports in Psychiatry, 2023)
While psychiatric manifestations are common in patients with Cushing’s syndrome (CS), to our knowledge, there are no reported cases of CS presenting with functional neurological disorder (FND), a neuropsychiatric condition in which patients experience neurological symptoms, such as motor dysfunctions, sensory symptoms, speech disorders, or nonepileptic seizures, in the absence of neurological disease. Here, we report a case of a complex patient with Cushing’s disease who presented with multiple FND symptoms including nonepileptic seizures, bilateral lower extremity paralysis, decreased finger flexion resulting in limited hand function, and stuttering. This case illustrates a rare psychiatric manifestation of CS presenting as multiple neurological complaints. Furthermore, we elucidate how a multidisciplinary treatment approach improved our patient’s FND symptoms.